The value of authenticity and intimacy: A case study of the Danish independent podcast Fries before Guys' utilization of Instagram. (1st April 2021) - Adler Berg, Freja Sørine
The article addresses podcasting as a social media activity, considering independent podcasters' ‐ an emerging but understudied category of Pro-Ams ‐ utilization of social media. This was done by conducting qualitative interviews (Brinkmann and Kvale 2001) with the Danish podcast phenomenon, Fries before Guys, and their main sponsor. To study the online interaction between listeners and podcasters, an inductive open coding of the podcast's Instagram account was carried out, focusing on the ten most-liked Instagram posts and the user comments written underneath. Since Instagram is the podcasters' primary means of communication in engaging socially with their mainly young female listeners, the aim was to explore how the digital infrastructure between Instagram and the podcast medium unfolds. The study shows that social media activity, besides providing emotional support through posts, comments and direct messages, is essential to independent podcasters to make revenue.